Substantial Downregulation of Myogenic Transcripts in Skeletal Muscle of Atlantic Cod during the Spawning Period - Nagasawa, Kazue; Sarropoulou, Elena; Edvardsen, Vigdis; Fernandes, Jorge M.O. (PLOS ONE, 2016)
Gonadal maturation is an extremely energy consuming process for batch spawners and it is associated with a significant decrease in growth and seasonal deterioration in flesh quality. Our knowledge about the molecular mechanisms linking sexual maturation and muscle growth is still limited. In the present study, we performed RNA-Seq using 454 GS-FLX pyrosequencing in fast skeletal muscle sampled from two-year-old Atlantic cod (Gadus morhua) at representative time points throughout the reproductive cycle (August, March and May). In total, 126,937 good quality reads were obtained, with 546 nucleotide length and 52% GC content on average. RNA-Seq analysis using the CLC Genomics Workbench with the Atlantic cod reference UniGene cDNA data revealed 59,581 (46.9%) uniquely annotated reads. Pairwise comparison for expression levels identified 153 differentially expressed UniGenes between time points. Notably, we found a significant suppression of myh13 and myofibrillar gene isoforms in fast skeletal muscle during the spawning season. This study uncovered a large number of differentially expressed genes that may be influenced by gonadal maturation, thus representing a significant contribution to our limited understanding of the molecular mechanisms regulating muscle wasting and regeneration in batch spawners during their reproductive cycle.